Limitations of rapid diagnostic tests in malaria surveys in areas with varied transmission intensity in Uganda 2017-2019: Implications for selection and use of HRP2 RDTs. - Agaba B Bosco; Joaniter I Nankabirwa; Adoke Yeka; Sam Nsobya; Karryn Gresty; Karen Anderson; Paul Mbaka; Christiane Prosser; David Smith; Jimmy Opigo; Rhoda Namubiru; Emmanuel Arinaitwe; et al. (PLoS ONE)
Background Plasmodium falciparum histidine-rich protein 2 (HRP2)-based rapid diagnostic tests (RDTs) are exclusively recommended for malaria diagnosis in Uganda; however, their functionality can be affected by parasite-related factors that have not been investigated in field settings. Methods Using a cross-sectional design, we analysed 219 RDT-/microscopy+ and 140 RDT+/microscopy+ dried blood spots obtained from symptomatic children aged 2-10 years from 48 districts in Uganda between 2017 and 2019. We aimed to investigate parasite-related factors contributing to false RDT results by molecular characterization of parasite isolates. ArcGIS software was used to map the geographical distribution of parasites. Statistical analysis was performed using chi-square or Fisher's exact tests, with P ≤ 0.05 indicating significance. Odds ratios (ORs) were used to assess associations, while logistic regression was performed to explore possible factors associated with false RDT results. Results The presence of parasite DNA was confirmed in 92.5% (332/359) of the blood samples. The levels of agreement between the HRP2 RDT and PCR assay results in the (RDT+/microscopy+) and (RDT-/microscopy+) sample subsets were 97.8% (137/140) and 10.9% (24/219), respectively. Factors associated with false-negative RDT results in the (RDT-/microscopy+) samples were parasite density (<1,000/μl), pfhrp2/3 gene deletion and non-P. falciparum species (aOR 2.65, 95% CI: 1.62-4.38, P = 0.001; aOR 4.4, 95% CI 1.72-13.66, P = 0.004; and aOR 18.65, 95% CI: 5.3-38.7, P = 0.001, respectively). Overall, gene deletion and non-P. falciparum species contributed to 12.3% (24/195) and 19.0% (37/195) of false-negative RDT results, respectively. Of the false-negative RDTs results, 80.0% (156/195) were from subjects with low-density infections (< 25 parasites per 200 WBCs or <1,000/μl). Conclusion This is the first evaluation and report of the contributions of pfhrp2/3 gene deletion, non-P. falciparum species, and low-density infections to false-negative RDT results under field conditions in Uganda. In view of these findings, the use of HRP2 RDTs should be reconsidered; possibly, switching to combination RDTs that target alternative antigens, particularly in affected areas, may be beneficial. Future evaluations should consider larger and more representative surveys covering other regions of Uganda.